(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article will explore the multifaceted role of teaching aids in foreign language teaching. It will examine their theoretical underpinnings in educational psychology and second language acquisition research, analyze their practical application across different language skills (listening, speaking, reading, and writing), and evaluate the impact of technological evolution on their nature and efficacy. Ultimately, the discussion aims to affirm that the thoughtful selection and implementation of teaching aids are not merely optional enhancements but indispensable components of effective, learner-centered, and successful foreign language instruction in the 21st century. The process of acquiring a foreign language presents a unique cognitive and cultural challenge, requiring learners to navigate unfamiliar phonetic, grammatical, and semantic landscapes. In this complex journey, the traditional model of instructor-centered instruction, relying predominantly on textbooks and verbal explanation, has increasingly proven insufficient to meet the diverse needs of modern learners. This realization has propelled teaching aids from a peripheral supplementary role to a central position in contemporary pedagogical practice.